2020
DOI: 10.14295/cs.v11i0.3196
|View full text |Cite
|
Sign up to set email alerts
|

Physiological indices and phytomass partition in precocious dwarf cashew clones irrigated with saline waters

Abstract: This research aimed to evaluate the physiological indices and the accumulation of phytomass in clones of precocious dwarf cashew under salt stress during rootstock formation. The experiment was conducted in greenhouse in the municipality of Pombal-PB. The experimental design was in randomized blocks, and the treatments were organized in a 5 x 3 factorial arrangement, constituting the levels of electrical conductivity of the irrigation water - ECw (0.4 -Control; 1.2; 2.0; 2.8, and 3.6 dS m-1) and the clones of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Such a decrease in RDP can be considered a strategy that plants use to reduce the absorption of toxic ions, especially Na + and Cl -, and their consequent transport to the aerial part of the plant, hampering plant growth (Sá, Mesquita, Bertino, Silva, & Costa, 2013). A reduction in root dry phytomass accumulation due to salt stress has also been observed in other crops such as cashew (Lima et al, 2020b) and guava (Sá et al, 2016). Londrina, v. 42, n. 1, p. 137-154, jan./fev.…”
Section: Table 2 Summary Of the Analysis Of Variance For Stomatal Conmentioning
confidence: 70%
“…Such a decrease in RDP can be considered a strategy that plants use to reduce the absorption of toxic ions, especially Na + and Cl -, and their consequent transport to the aerial part of the plant, hampering plant growth (Sá, Mesquita, Bertino, Silva, & Costa, 2013). A reduction in root dry phytomass accumulation due to salt stress has also been observed in other crops such as cashew (Lima et al, 2020b) and guava (Sá et al, 2016). Londrina, v. 42, n. 1, p. 137-154, jan./fev.…”
Section: Table 2 Summary Of the Analysis Of Variance For Stomatal Conmentioning
confidence: 70%
“…The maximum reduction was observed in plants subjected to spray with the estimated H 2 O 2 concentration of 32 μM (RDB=11.19 g plant -1 ). From the estimated H 2 O 2 concentration of 33 μM, there was an upward trend in RDB, similar to LDB, which diversion of energy destined for growth to activate and maintain membrane integrity, synthesis of organic solutes for osmoregulation, and/or protection of macromolecules and regulation of ionic transport and distribution in various organs within cells (Lima et al, 2020).…”
Section: Tablementioning
confidence: 86%
“…Lucena, Negreiros, Medeiros, Grangeiro, & Marrocos (2011) examined the growth of another curcubit, 'Quetzali' watermelon, grown under field conditions, using water with different salinity levels, and also found that water with higher electrical conductivity (3.98 dS m -1 ) reduced the accumulation of dry biomass, thus reducing plant growth. The reduction in biomass accumulation may be related to the decrease in chlorophyll levels, the photosynthetic rate of plants, and the diversion of energy destined for growth to activate and maintain membrane integrity, synthesis of organic solutes for osmoregulation, and/or protection of macromolecules and regulation of ionic transport and distribution in various organs within cells (Lima et al, 2020).…”
Section: Tablementioning
confidence: 99%
“…Cashew (Anacardium occidentale L.) is a fruit crop widely cultivated in Brazil, especially in the semiarid region of the Northeast, having great socioeconomic importance in the generation of employment and income (Lima et al, 2020a;Sousa et al, 2023). The Northeast of Brazil has a planted area of approximately 616,189 ha and accounts for about 99% of the national production, having the states of Ceará (42,597 tons), Rio Grande do Norte (33,912 tons) and Piauí (28,292 tons) as main producers (Suassuna et al, 2017).…”
Section: Introductionmentioning
confidence: 99%